Digital Marketing and QRIS Implementation for Culinary MSME Promotion - Sumiati Sumiati; Yunelly Asra (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia's culinary sector calls for structured promotional platforms that connect local businesses with wider markets. This study reports the implementation of Polbeng Business Expo Chapter II, a three-day exhibition held in Bengkalis in May 2025, focusing on the liaison officer and business consultant roles assigned to two culinary MSMEs, Bakso Mama Via and Rujak Indah. The project applied the marketing mix framework (4P and 7P) together with digital marketing content business profile videos, promotional videos, digital catalogs, and the QRIS cashless payment system to strengthen the two MSMEs' market visibility and transaction efficiency. A descriptive, project-based case study method was used, covering preparation, implementation, accomplishment, and reporting stages, supported by documentation and simple financial recording. The results show that both MSMEs obtained a stronger brand identity and wider digital exposure through social media promotion, although their sales performance during the expo diverged: Rujak Indah recorded a revenue increase from the pre-expo period, while Bakso Mama Via experienced a decline. These findings indicate that structured promotional assistance and digital payment adoption can enhance MSME competitiveness, even though sales outcomes remain influenced by product type, location, and consumer preference to choices.